Modeling Nitrogen Uptake in Eight Common Leafy Vegetables in Red River Delta, Vietnam - Lan Huong Nguyen Thi; Lim Duong Thi; Oudomphone Insixiengmai; Toan Nguyen-Sy (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Fertilizer originated nitrate excess in vegetables has attracted numerous studies for its effects on food quality. However, the relationship between plant nitrate accumulation and fertilizer-derived nitrogen (FTN) in the soil in continuous research is rarely reported. This study examines the impact of conventional ammonium fertilizer application (50.4 kg/ha) on the constant trend of soil nitrogen and plant nitrate uptake of 8 common leafy vegetables grown in Red Delta River, Vietnam. The vegetables reveal both FTN and plant nitrate took about 17 days to release from topsoil and plant. The trend of FTN is well fitted by a regression model (Decay model, R2=0.945, p<0.001), which shows the nitrogen loss rate of FTN range from 0.120-0.139 g N/day. Meanwhile, the trend of plant nitrate uptake fitted the quadratic equation (R2=0.889, p<0.01). Although the correlation between FTN and plant nitrate is weak, this study finds that autumn crops have a tighter relationship than summer crops (R=0.71 and R=0.46, respectively). It can be concluded that regression models could be suitable methods to observe the behavior of fertilizer nitrogen in soil and vegetable uptake.